2020
DOI: 10.1634/theoncologist.2019-0031
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Prognosis of Pneumonia in Patients with Solid Tumors: A Prospective Cohort of Hospitalized Cases

Abstract: Background. Data on the incidence, etiology, and prognosis of non-ventilator-associated pneumonia in hospitalized patients with solid tumors are scarce. We aimed to study the characteristics of non-ventilator-associated pneumonia in hospitalized patients with solid tumors. Materials and Methods. This was a prospective noninterventional cohort study of pneumonia in patients hospitalized in an oncology ward in a tertiary teaching hospital. Pneumonia was defined according to the American Thoracic Society criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(26 reference statements)
0
4
0
1
Order By: Relevance
“…Substantial data suggest that hypoxia is involved in promoting tumorigenesis [33] , progression [34] , and maintenance of malignant phenotype [35] . For example, the pressure of hypoxia provides an adaptation process of tumour cells reprogramming, contributing to proliferation, migration and invasion [36] , [37] , [38] . Studies also confirmed that hypoxia plays an important role in reprogramming TIM [39] , [40] , [41] , [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Substantial data suggest that hypoxia is involved in promoting tumorigenesis [33] , progression [34] , and maintenance of malignant phenotype [35] . For example, the pressure of hypoxia provides an adaptation process of tumour cells reprogramming, contributing to proliferation, migration and invasion [36] , [37] , [38] . Studies also confirmed that hypoxia plays an important role in reprogramming TIM [39] , [40] , [41] , [42] .…”
Section: Discussionmentioning
confidence: 99%
“…En el caso de la VAP los factores de riesgo más comunes son la existencia de enfermedad pulmonar subyacente, inmunosupresión, edad mayor de 70 años, posición supina, reintubación, disfagia y cirugía torácica o abdominal reciente [25,26]. En los pacientes con cáncer aumenta tanto la incidencia de neumonía como la mortalidad [27].…”
Section: Neumoníaunclassified
“…Diagnosis of pneumonia based on clinical symptoms, which may be poorly expressed in oncologic patients, may be difficult ( Wong and Ewans 2017 ). Therefore, well-documented risk factors for mortality in pneumonia, such as an unidentified etiology ( Azoulay et al 2017 ), a delay in antibiotic administration in patients with severe disease ( Nauclér et al 2021 ), and the inappropriate antimicrobial empiric therapy ( Fernandez-Cruz et al 2020 ) are of particular importance among these patients. Pneumonia can be caused by many pathogens, making empiric antibiotic therapy difficult ( Leoni et al 2016 ; Conway 2018 ).…”
Section: Introductionmentioning
confidence: 99%